Enhanced CO2 bio-utilization with a liquid–liquid membrane contactor in a bench-scale microalgae raceway pond. (December 2019) - Xu, Xiaoyin; Martin, Gregory J.O.; Kentish, Sandra E.
Highlights: CO2 delivered to microalgae via liquid–liquid membrane contact with a CO2 loaded solvent. Mass transfer was limited by the wetting of the porous membrane support. A pond liner made from flat sheet membranes provided better CO2 delivery than hollow fibers. pH control limited the CO2 ventilation loss, leading to 90% CO2 utilisation. Abstract: Microalgae are able to absorb CO2 generated from sources such as flue gas to produce biomass with high lipid content. In this research, an immersed liquid–liquid membrane contactor was investigated to deliver CO2 captured by a chemical solvent to the microalgae culture via semipermeable membranes. Experiments showed that the CO2 mass transfer could be facilitated by using a thinner membrane support layer, or avoiding a support altogether, as the support was liquid filled which reduced the mass transfer coefficient. In order to better condition the culture media, the solvent flow was controlled by pH feedback. This scenario showed comparable biomass productivity (0.10 g L −1  d −1 ) to the conventional direct bubbling method, but with a lower energy cost and higher CO2 utilization efficiency. Further, a pond liner was formed from flat sheet membranes as a more effective alternative to a hollow fiber arrangement. The optimized system achieved a CO2 utilization efficiency of up to 90% compared to 47% with the uncontrolled hollow fiber membrane system and 11% for air sparging, thereby reducing the CO2 released to the atmosphere.